2017
DOI: 10.1136/bmjopen-2017-017814
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Canadian parents' HPV vaccine knowledge, attitudes and behaviour: a study protocol for a longitudinal national online survey

Abstract: IntroductionHuman papillomavirus (HPV), a sexually transmitted infection, can cause anogenital warts and a number of cancers. To prevent morbidity and mortality, three vaccines have been licensed and are recommended by Canada’s National Advisory Committee on Immunisation (for girls since 2007 and boys since 2012). Nevertheless, HPV vaccine coverage in Canada remains suboptimal in many regions. This study will be the first to concurrently examine the correlates of HPV vaccine decision-making in parents of schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…Details of the methodology are presented in the protocol paper. 20 This study used a crosssectional design to collect self-reported online survey data from a national sample of Canadian parents. Data presented here were part of a larger two-wave protocol and were collected from August 17 to September 11, 2016 (i.e.…”
Section: Survey Design and Participantsmentioning
confidence: 99%
See 3 more Smart Citations
“…Details of the methodology are presented in the protocol paper. 20 This study used a crosssectional design to collect self-reported online survey data from a national sample of Canadian parents. Data presented here were part of a larger two-wave protocol and were collected from August 17 to September 11, 2016 (i.e.…”
Section: Survey Design and Participantsmentioning
confidence: 99%
“…27 This study received Research Ethics Board approval from the Research Review Office, Integrated Health and Social Services University Network for West-Central Montreal (CODIM-FLP-16-219). 20…”
Section: Survey Design and Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, nearly 75% "somewhat" to "strongly" disagreed that vaccinating their son for HPV would send a message that he would not have to use safe sex practices, with only 11.1% of parents saying that they somewhat to strongly agreed that it would (unpublished data). Correspondingly, in a national study of 3779 parents of 9-to 16-year-old boys and girls across Canada [112], fewer than 7% of parents "somewhat" to 9/4/2018 11/32…”
Section: Risk Compensationmentioning
confidence: 99%